Nitro-oleic acid reduces thoracic aortic aneurysm progression in a mouse model of Marfan syndrome. Issue 9 (29th July 2021) - Nettersheim, Felix Sebastian; Lemties, Julian; Braumann, Simon; Geißen, Simon; Bokredenghel, Senai; Nies, Richard; Hof, Alexander; Winkels, Holger; Freeman, Bruce A; Klinke, Anna; Rudolph, Volker; Baldus, Stephan; et al.
Abstract: Aims: Marfan syndrome (MFS) is a connective tissue disorder caused by mutations in the Fibrillin-1 gene. It is associated with formation of thoracic aortic aneurysms that can potentially be a life-threatening condition due to aortic rupture or dissection. Excessive non-canonical transforming growth factor beta signalling, mediated by activation of extracellular signal-regulated kinases 1/2 (ERK1/2), as well as inducible nitric oxide synthase (NOS2)-dependent nitric oxide production, have been identified to drive aortic pathology in MFS through induction of elastin fragmentation and smooth muscle cell apoptosis. Despite promising results in animal studies, specific pharmacological interventions approved for clinical use in patients with MFS-related aortic disease are rare. Nitro-oleic acid (NO2 -OA) is an endogenously generated signalling modulator, which is available as an oral compound and has been shown to inhibit ERK1/2 activation and NOS2 expression in different disease models, thereby exerting promising therapeutic effects. In this study, we investigated whether NO2 -OA decreases aortic dilation in MFS. Methods and results: Eight-week-old MFS ( Fbn1 C1041G/+ ) mice were treated with NO2 -OA or vehicle for 4 weeks via subcutaneously implanted osmotic minipumps. Echocardiography indicated progressive ascending aortic dilation and wall stiffening in MFS mice, which was significantly attenuated by NO2 -OA treatment. This protective effect was mediated by inhibition of aortic ERK1/2, Smad2 as well as nuclear factor kappa B overactivation and consequent attenuation of elastin fragmentation by matrix metalloproteinase 2, apoptosis, and collagen deposition. Critically, the therapeutic efficacy of NO2 -OA in MFS was further emphasized by demonstrating its capability to reduce lethal aortic complications in Fbn1 C1041G/+ mice challenged with Angiotensin II. Conclusion: NO2 -OA distinctly attenuates progression of aortic dilation in MFS via modulation of well-established disease-mediating pathways, thereby meriting further investigation into its application as a therapeutic agent for the treatment of this condition. Graphical Abstract: